2021
DOI: 10.3390/en14113245
|View full text |Cite
|
Sign up to set email alerts
|

Regional Solar Irradiance Forecast for Kanto Region by Support Vector Regression Using Forecast of Meso-Ensemble Prediction System

Abstract: From the perspective of stable operation of the power transmission system, the transmission system operators (TSO) needs to procure reserve adjustment power at the stage of the previous day based on solar power forecast information from global horizontal irradiance (GHI). Because the reserve adjustment power is determined based on information on major outliers in past forecasts, reducing the maximum forecast error in addition to improving the average forecast accuracy is extremely important from the perspectiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 37 publications
(40 reference statements)
0
9
0
Order By: Relevance
“…and day‐ahead forecasting of aggregated PV power within a certain region using support vector regression (SVR) by Fonseca et al 8 . As regards forecasting based on MEPS, Takamatsu et al 9 . realized prediction by SVR using GHI forecast by MEPS and multiple elements of MSM; in so doing, they evaluated both large errors and average errors 9 .…”
Section: Forewordmentioning
confidence: 99%
See 2 more Smart Citations
“…and day‐ahead forecasting of aggregated PV power within a certain region using support vector regression (SVR) by Fonseca et al 8 . As regards forecasting based on MEPS, Takamatsu et al 9 . realized prediction by SVR using GHI forecast by MEPS and multiple elements of MSM; in so doing, they evaluated both large errors and average errors 9 .…”
Section: Forewordmentioning
confidence: 99%
“…As regards forecasting based on MEPS, Takamatsu et al 9 . realized prediction by SVR using GHI forecast by MEPS and multiple elements of MSM; in so doing, they evaluated both large errors and average errors 9 . In addition, Nohara et al 10 .…”
Section: Forewordmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies applied the EPS output from European Center for Medium-Range Weather Forecasts (ECMWF) to machine learning models; S. Sperati et al adopted NN for the post-processing of the ECMWF EPS forecasts for their photovoltaic power forecasting [49], S. Rasp and S. Lerch also employed NN on ECMWF's EPS forecasts for temperature estimation [50], and L. Massidda and M. Marrocu used QR with Gradient-Boosted Regression Trees (GBRT) to each EPS member and combined their output with Integrated Forecast System (IFS) data [51]. In Japan, the MEPS data, which is based on the MSM data from JMA was used, and several studies were reported, including the study of confidence interval estimation using the Just-in-Time model [52] and the study of postprocessing methods for EPS data based on support vector machines [53]. These studies show that EPS data helps to improve the accuracy of PV forecasts.…”
Section: Stochastic Approach Based On Ensemble Prediction Systemmentioning
confidence: 99%
“…These studies show that EPS data helps to improve the accuracy of PV forecasts. In particular, our recent article [53] suggests that the maximum (minimum) forecast error can be suppressed by the EPS output as an explanatory variable in the SVR.…”
Section: Stochastic Approach Based On Ensemble Prediction Systemmentioning
confidence: 99%